Layer by Layer Deposition of 1T′‐MoS2 for the Hydrogen Evolution Reaction. Issue 7 (17th February 2022) - Alimohammadi, Farbod; Yasini, Parisa; Marshall, Tim; Attanayake, Nuwan H.; Borguet, Eric; Strongin, Daniel R.
Abstract: The layer by layer (LbL) method has been used to assemble catalytic materials for the electrochemical hydrogen evolution reaction (HER). The electrocatalytic activity of LbL deposited 1T′‐MoS2 (metallic phase) on a fluorine‐doped tin oxide substrate was investigated for the HER as a function of the number of deposition layers (mass loading). The morphology, thickness, and roughness of the deposited MoS2 layers as a function of the number of deposition layers were investigated using atomic force microscopy and scanning electron microscopy. The average roughness of the surface increased with the number of deposition layers, indicating that the thickness of the deposited layered material became heterogeneous with increasing layer number. The primary conversion of the deposited 1T′‐MoS2 to the semiconducting 2H‐MoS2 phase via exposure to 532 nm wavelength light, confirmed by Raman spectroscopy and scanning tunneling spectroscopy, allowed a comparison of the HER activity of the two phases at a constant mass loading and surface area on the same substrate. For a given number of deposition layers (i. e., similar mass loading), 1T′‐MoS2 exhibited a lower overpotential for the HER than the 2H‐MoS2 (with a minority 1T′ component) phase. For example, at a sample thickness of 19.7±2.8 nm (20 LbL layers) the overpotentials for the HER for submonolayer amounts of 1T′‐MoS2 and after exposure to 532 nm light were 0.54 and 0.61 V, respectively (at a current density of −2 mA/cm 2 ). Overall, the overpotential for HER associated with both MoS2 phases decreased as the mass loading increased. Abstract : Caption: 1T′‐MoS2 layers were assembled on various substrates by the layer‐by‐layer technique. Atomic force microscopy analysis of the assembled films confirmed that the height of the MoS2 layers increased with each deposition layer. The hydrogen evolution reaction performance improved as the number of layers making up the electrocatalyst increased.